Literasi Digital Marketing dan Pemanfaatan Marketplace dalam Pengembangan Bisnis Online di SMK Pangeran Antasari Kota Medan - Dennys Paulus P Damanik; Demak Claudia Yosephine Simanjuntak; Yois Nelsari Malau; Nina Purnasari; Keumala Hayati (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
The background of digital marketing literacy and the use of marketplaces in online business development at Prince Antasari Vocational School, Medan City is to be able to introduce students in the school environment to the importance of using digital roles in online business development. This is because many people want to open micro, small and medium enterprises, but have difficulty marketing the products they produce. With the development in the field of technology and information, it is a solution to this problem. Where people can market their products through social media and other online applications. This results in a very broad marketing area coverage and is expected to enable micro, small and medium enterprises to develop rapidly and open wide job vacancies as well. Therefore this service activity is aimed at students at Prince Antasari Vocational School because of the background of the participants who come from lower middle class families. It is hoped that with this activity the participants can add insight and pass it on to their families and the people around them. This service activity is carried out at Prince Antasari Vocational School, Medan City, which is located at Veteran Street no. 106, Helvetia, Labuhan Deli sub-district, Deli Serdang district, North Sumatra 20373. The purpose of this activity is to introduce digital roles and how to put them into practice in online business development. The result of this activity is the enthusiasm of students at Prince Antasari Vocational School in doing online business as well as an increase in knowledge and interest in doing business online. The method used is to conduct direct presentations by resource persons using powerpoints and also by distributing questionnaires before and after the presentation.